Effects of κ-opioid receptor agonists on long-term cocaine use and dopamine neurotransmission - Collins, Stephanie L; D'Addario, Claudio; Izenwasser, Sari (European journal of pharmacology, 2001)
κ-Opioid receptor agonists have been suggested as treatments for cocaine addiction based on studies showing that they block cocaine-related behaviors. To determine the effects of κ-opioid receptor agonists on long-term behavioral effects associated with cocaine and the neurochemical bases underlying these effects, rats were treated with the selective κ-opioid receptor agonist U-69593 ((+)(5α,7α,8β)- N-methyl- N-[7-(1-pyrrolidinyl)-1 oxaspiro[4.5]dec-8-yl]-benzeneacetamide) alone or in combination with cocaine and locomotor activity was measured daily. In addition, dopamine transporter and dopamine receptor densities were measured using autoradiographic techniques, and tyrosine hydroxylase was measured using immunoautoradiographic techniques. Treatment with U-69593 with or without cocaine decreased locomotor activity. When challenged with cocaine after a 5-day treatment period, the effects of cocaine were markedly reduced in rats initially treated with U-69593 compared to vehicle. When U-69593 was administered five times with 3-day intervals, it alone had no effect on locomotor activity but still reduced activity associated with a cocaine injection. After five daily injections, U-69593 decreased dopamine transporter and dopamine D 2 receptor densities and increased tyrosine hydroxylase levels. These changes were not seen after the 3-day interval regimen, even though cocaine-induced activity was greatly reduced. These findings show that the effects associated with daily U-69593 treatment are attenuated if the drug is administered with a greater interval, while maintaining a blockade of cocaine-induced activity. In addition, U-69593 can block cocaine-induced locomotor effects without major perturbation of the dopamine system.